Dehiscensicoridae fam. nov. (Insecta: Heteroptera: Pentatomomorpha) from the Upper Mesozoic of Northeast China. (2nd December 2017) - Du, Sile; Yao, Yunzhi; Ren, Dong; Zhang, Weiting
Abstract : A new family of insects is described from the Lower Cretaceous Yixian Formation in western Liaoning Province, China. Dehiscensicoridae Du, Yao & Ren fam. nov. comprises five new genera and five new species: Dehiscensicoris sanctus Du, Yao & Ren gen. et sp. nov., Pingquanicoris punctatus Du, Yao & Ren gen. et sp. nov., Changirostrus maculatus Du, Yao & Ren gen. et sp. nov., Crassiantenninus minutus Du, Yao & Ren gen. et sp. nov. and Minuticoris brunneus Du, Yao & Ren gen. et sp. nov. A cladistic analysis based on a combination of fossil and extant morphological characters is used to hypothesize the phylogenetic status of the new family, allowing the reconstruction of the interfamily relationships within the Coreoidea ( sensu lato ) which were found to be: Pyrrhocoroidea + (Dehiscensicoridae fam. nov. + (Coreoidea + (Idiostoloidea + Lygaeoidea))). http://zoobank.org/urn:lsid:zoobank.org:pub: E501B670-AF36-408C-8B9D-466B330BA775